ASSESSMENT OF PROTEOLYTIC ACTIVITY OF THE AQUEOUS LEAF EXTRACT OF Clerodendrum colebrookianum AND ITS EFFECT ON THE BLOOD COAGULATION CASCADE - SARMAH, PUJA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Clerodendrum colebrookianum is a highly medicinal plant. Plant protease is one of the main components of analyzing the anticoagulant property of the plant. From the gelatin-agar plate, the technique confirms the presence of protease activity in Clerodendrum colebrookianum. Enzymatic activity and specific enzyme activity of the aqueous extract were determined using the caseinolytic method. It was seen that the enzyme activity (U) of Clerodendrum colebrookianum is 0.99±0.004 µmol of tyrosine released/ml/min. For the aqueous leaf extract of Clerodendrum colebrookianum the Clotting Time (CT), Prothrombin Time (PTT) and activated Partial Thromboplastin Time (aPTT) was determined and it was found that the plasma recalcification time increases the normal clotting time significantly at the dose of 1µG but not significant at dose 5 µg. The prothrombin time of the crude aqueous extracts of CC was observed to increase the prothrombin time significantly at the dose of 1µG. The activated partial thromboplastin time was seen to be insignificant in Clerodendrum colebrookianum. Even though Clerodendrum colebrookianum may act as a significant anticoagulant in the common and extrinsic pathways; on the intrinsic pathway of the blood coagulation cascade it may not have any effect.